Study of mechanical behavior and self-cementing properties of recycled concrete aggregates under repeated loading - Wang, Chong; Chazallon, Cyrille; Hornych, Pierre; Jing, Peng; Mouhoubi, Saida (CCSD, 2023)
International audience It is known that the strength and stiffness of unbound base and subbase layers prepared with recycled concrete aggregates (RCA) increase over time, known as self-cementing properties of RCA. However, the influence of self-cementing properties on the permanent and resilient deformation behavior has not been thoroughly studied. In this study, the permanent and resilient deformation behavior of two RCA, ORCA and NRCA (old and fresh crushed RCA), after different curing times (1, 180, 360 and 720 days), were investigated by conducting a series of repeated load triaxial tests. The results show that the permanent deformation of NRCA, crushed recently, decreases to a negligible value after curing 180 days, and then reaches a constant value. While the resilient modulus of NRCA increases steadily with curing time till the studied curing time (720 days). Besides, the long-term storage reduces the self-cementing properties of ORCA. As a result, the negligible self-cementing properties have no influence on the permanent and resilient deformation behavior of ORCA.